The integral autoseroterapia in human microbiosis - Escomel, Edmundo (1921)
The integral autoseroterapia is the therapeutic method is to use the patient's serum at the time of infection to heal. Imitates nature taking advantage of the medium that it brings into play to combat human microbiosis. Tends to destroy the dream harmful actions and leaving only the healing to use them successfully.